Audit Aset Produktif pada PT. XYZ - Yulia Ayu Puspita Hutagalung; Damayanti Damayanti; Dian Nirmala Dewi (Jurnal Ilmiah ESAI, 2021)
This writing aims to describe the classification of plants that have not produced that should be used as producing plants or categorized into assets. The data used is secondary data using documentation data collection methods. The data analysis method carried out by the author is to collect data related to auditing productive assets such as pt xyz financial statements, working papper audit, draft audit of PT XYZ in 2019, and a list of details of TBM and TM. Then study the audit of productive assets in accordance with the procedures of KAP KS, perform a recalculation of productive assets, and present the findings obtained by the auditor and present the audit results. From the results and discussions that have been done by the author, it can be concluded that the auditor has done calculations related to the productive assets of PT XYZ and the results obtained from the audit conducted by kap KS auditors, namely PT XYZ has not made Plants Have Not Produced into Producing Plants. So it is recommended 2 journal adjustment related to its findings when conducting an audit of pt xyz's productive assets